A report on the practice in industry training in fish preservation. - Cichon, Melchor F. (1970.)
Philippine waters are rich in natural resources - especially fish and other fishery materials. Yet, it is deplorable to note that Filipinos are still importing huge amounts of canned fish and other fishery products in spite of such abundance. The Fisheries Statistics of the Philippines, an official publication of the Philippine Fisheries Commission, points out that in 1965, the Philippine government imported P61, 696, 012 worth of canned fish and other fishery products. The same source predicts that the government will still import a huge amount of fishery products as seen from our present production. ¹ "The fish supply," according to the Philippine Fisheries Commission, "is 667, 202 metric tons yearly."² "This is short of 32.7% of the total amount required for 32, 700, 000 Filipinos."³ To fill this gap, our government had to import 51, 730, 589 kilograms of fish whose monetary value amounts to P61, 692, 000.4 Lack of food is one of the most serious problems confronting our nation. If we have been critical enough with our observation on Philippine contemporary events, this problem of lack of food is one of the root causes of the most serious crimes committed in our country. Therefore, "It is incumbent," says Wesley C. Heraldson, Director of the USAID mission in the Philippines, "upon every educated citizen to look at this problem seriously and honestly - without bias and opinion - to assure that too little is not done too late." The U.P. College of Fisheries offers some courses for the proper preservation, utilization, and upliftment of our fishery resources products. Aside from teaching them the fundamentals of the basic sciences, the students of the College of Fisheries of the University of the Philippines are taught, instructed, supervised scientifically by competent instructors and professors the modern trends and practical skills on fishery industries and researches. This is done purposely to enable the students to become proficient fishery educators, fishery researchers, fishery businessmen or any combination of these three. Apprenticeship is a way of augmenting and polishing the knowledge that the students have acquired and mastered from their classrooms. Thus, every graduating fishery student is required to undergo a four-month practice-in-industry both in the laboratory of the College of Fisheries of the University of the Philippines and in the laboratories of other public and private fishery firms. Aside from the training that they get from this apprenticeship, the graduating students have the opportunity to get acquainted with the owners of the aforementioned firms; henceforth paving a way of finding an immediate employment.
Report (Undergraduate. Fish Preservation) Philippine Institute of Fisheries Technology, Diliman. 1970..
Keywords: Fish capture